HUBUNGAN ANTARA KUALITAS PELAYANAN LEMBAGA PENYEDIA SAPRODI DENGAN PREFERENSI DAN KEPUASAN PELANGGAN - Mirnawati Mirnawati; Marcelinus Molo; Suminah Suminah (AGRITEXTS: Journal of Agricultural Extension, 2016)
The  purposes  of  this  research  are  to  know  the  service  quality  of  the production medium supplier organizations, the chosen location to fulfill the farmer needs; the farmers’ reasons  in choosing KUD, agriculture shops or shops to fulfill the farmer needs. The basic method used in this research is descriptive with survey. The sample are taken by simple random sampling and the decision of the mount each village are done proportionally with 60 respondents of farmers. The analysis to know the relationship among variable is use correlation coefficient of rank spearman and uses t test with (α=0,005). The result of rank spearmen analysis shows that the relationship between the service quality of the production medium supplier organization with preference and the customers’ satisfaction are the most significant. While, the relationship between agriculture shops, which is seen from worker performance, variety of product, and availability of the production medium are not significant which is the trust (α=0,005). In analysis of rank spearman also is found that the relationship between the quality of shop service and the costumers’ preference are not significant, but the relationship between the worker performance and the costumer’s satisfaction are the most significant and the relationship between variety of product and the availability of the production. medium in he shops with the costumers’ satisfaction.